Vaccination Patterns in Children After Autism Spectrum Disorder Diagnosis and in Their Younger Siblings - Zerbo, Ousseny; Modaressi, Sharareh; Goddard, Kristin; Lewis, Edwin; Fireman, Bruce H; Daley, Matthew F; Irving, Stephanie A; Jackson, Lisa A; Donahue, James G; Qian, Lei; Getahun, Darios; DeStefano, Frank; et al. (JAMA pediatrics, 2018)
In recent years, rates of vaccination have been declining. Whether this phenomenon disproportionately affects children with autism spectrum disorder (ASD) or their younger siblings is unknown. To investigate if children after receiving an ASD diagnosis obtain their remaining scheduled vaccines according to the Advisory Committee on Immunization Practices (ACIP) recommendations and to compare the vaccination patterns of younger siblings of children with ASD with the vaccination patterns of younger siblings of children without ASD. This investigation was a retrospective matched cohort study. The setting was 6 integrated health care delivery systems across the United States within the Vaccine Safety Datalink. Participants were children born between January 1, 1995, and September 30, 2010, and their younger siblings born between January 1, 1997, and September 30, 2014. The end of follow-up was September 30, 2015. Recommended childhood vaccines between ages 1 month and 12 years. The proportion of children who received all of their vaccine doses according to ACIP recommendations. The study included 3729 children with ASD (676 [18.1%] female), 592 907 children without ASD, and their respective younger siblings. Among children without ASD, 250 193 (42.2%) were female. For vaccines recommended between ages 4 and 6 years, children with ASD were significantly less likely to be fully vaccinated compared with children without ASD (adjusted rate ratio, 0.87; 95% CI, 0.85-0.88). Within each age category, vaccination rates were significantly lower among younger siblings of children with ASD compared with younger siblings of children without ASD. The adjusted rate ratios varied from 0.86 for siblings younger than 1 year to 0.96 for those 11 to 12 years old. Parents who had a child with ASD were more likely to refuse at least 1 recommended vaccine for that child's younger sibling and to limit the number of vaccines administered during the younger sibling's first year of life. Children with ASD and their younger siblings were undervaccinated compared with the general population. The results of this study suggest that children with ASD and their younger siblings are at increased risk of vaccine-preventable diseases.